Impact of green factors on undergraduate students’ green behavioral intentions: A hybrid two-stage modeling approach - Sanjoy Kumar Roy (Heliyon, 2023)
Consumers' unsustainable behavior contributes to environmental degradation and impedes sustainability. Using green products is one way to reduce this effect and promote environmental growth. Therefore, this study aims to investigate the green factors that impact young customers' behavioral intentions regarding green products. For this purpose, the researcher designed a research model based on the expanded theory of planned behavior (TPB). The study adopted a two-stage, hybrid model using partial least square-structural equation modeling (PLS-SEM) and necessary condition analysis (NCA) to evaluate and validate the results. A sample of 382 undergraduate students was gathered using a convenience sampling approach. The results reveal that green TPB perception (GTP), green price sensitivity (GPS), green product trust (GPT), and green product value (GPV) are significantly and positively correlated with green behavioral intention (GBI). This study's main contribution is adding a brand-new higher-order construct, GTP, in the environmental and marketing literature and validating its effect on GBI. Again, environmental awareness moderates the association between GPS and GBI. Furthermore, the NCA's findings indicated that these variables are necessary to various degrees for students' GBI. Decision-makers may use the study's insights to create successful regulations to better understand young customers and develop appropriate green initiatives for sustainable development.